Swedish Pension Reforms in the 1990s - N. Anders Klevmarken (Uppsala University, Department of Economics, 2002)
Many Western countries with an aging population consider reforms of their pay-as-you-go pension systems. In Sweden a new pension system has already been decided and implemented. This paper gives a brief background to the Swedish reforms in the 1990s and explains the structure of the new system.
urn:nbn:se:uu:diva-2226
Keywords: H55; 330; Pensons; pay-as-you-go; notional defined pensions; pension reform; Rentenreform; Umlageverfahren; Schweden